2020
DOI: 10.3390/cancers12030636
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between HER2 and PD-1/PD-L1 in Breast Cancer: From Clinical Applications to Mathematical Models

Abstract: Breast cancer is one of the major causes of mortality in women worldwide. The most aggressive breast cancer subtypes are human epidermal growth factor receptor-positive (HER2+) and triple-negative breast cancers. Therapies targeting HER2 receptors have significantly improved HER2+ breast cancer patient outcomes. However, several recent studies have pointed out the deficiency of existing treatment protocols in combatting disease relapse and improving response rates to treatment. Overriding the inherent actions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 187 publications
(331 reference statements)
1
43
0
4
Order By: Relevance
“…Results from the immunostaining analysis revealed that PD-L1 expression in TILs and cancer cells was higher in HER2-positive mammary carcinoma, as reported in humans [ 2 , 3 , 16 , 20 , 22 ], contrasting with TN mammary carcinoma tumor samples. In spite of our findings, previous studies in human breast cancer showed that PD-1 and PD-L1 positive TILs and cancer cells overexpressing PD-L1 were frequently found in triple negative breast cancer subtype [ 16 , 23 , 38 , 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Results from the immunostaining analysis revealed that PD-L1 expression in TILs and cancer cells was higher in HER2-positive mammary carcinoma, as reported in humans [ 2 , 3 , 16 , 20 , 22 ], contrasting with TN mammary carcinoma tumor samples. In spite of our findings, previous studies in human breast cancer showed that PD-1 and PD-L1 positive TILs and cancer cells overexpressing PD-L1 were frequently found in triple negative breast cancer subtype [ 16 , 23 , 38 , 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 63%
“…At the molecular level, there are distinct subtypes of breast cancer: Luminal A, Luminal B, HER2-positive and triple-negative (normal-like and basal-like) [ 2 ]. The HER2-positive subtype is characterized by a HER2 overexpression and a lack of hormone receptors (estrogen receptor (ER) and/or progesterone receptor (PR)), while the triple negative tumors are defined by the absence of ER, PR and HER2 expression, each representing 15–20% of all breast cancer cases [ 1 , 3 ]. As in human breast cancer [ 4 ], FMC presents an aggressive and infiltrative behavior [ 5 , 6 ], with both HER2-positive and triple negative (TN) subtypes showing worse prognosis than luminal A and B subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…ALIX downregulation promotes tumor survival through enhancement of EGFR activation, and through PD-L1 membrane accumulation, leading to immunosuppression 73 . In HER2-enriched breast cancer, the crosstalk between HER2 and PD-L1 is poorly understood 74 . However, in HER2-positive breast cancer cells cocultured with human peripheral blood mononuclear cells and in a mouse model, trastuzumab anti-HER2 therapy resulted in upregulation of PD-L1 75 , 76 .…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that PD-1/PD-L1 checkpoint therapies could be greatly improved in TNBC with the employment of inhibitors of EMT and metabolic reprogramming of CAR T cell therapies, as well as the avoidance of the combination of PD-1/PD-L1 therapies with chemotherapeutic agents. The use of mathematical models that incorporate tumor-immune cell dynamics might provide quantitative representations of the phenomena involved in cancer progression [ 171 ]. This approach would be useful to mimic molecular networks and to search for novel networks.…”
Section: Resultsmentioning
confidence: 99%